Proposed Economic Journal in England (Quarterly Journal of Economics, 1887)
Journal Article Proposed Economic Journal in England Get access The Quarterly Journal of Economics, Volume 2, Issue 1, October 1887, Page 64, https://doi.org/10.1093/qje/2.1.64 Published: 01 October 1887